Properties of Self-Compacting Mortar Containing Slag with Different Finenesses - Siham Hammat; Belkacem Menadi; Said Kenai; Jamal Khatib; El-Hadj Kadri (Salehan Institute of Higher Education, 2021)
It is well established that Self-Compacting Concrete (SCC) contains large amounts of fines including mineral admixtures, such as fly ash and slag, in order to avoid segregation and to increase cohesion. The use of these materials in concrete reduces CO2 emissions and contributes towards sustainable construction. To overcome the negative effect of slag on the strength development slag was ground to three finenesses. Therefore, this paper examines the rheological, compressive strength, total and autogenous shrinkage and capillary water absorption of Self-Compacting Mortars (SCM) containing ground granulated blast furnace Slag (S). A total of seven mortar mixes were prepared. The control mix had a proportion of 1 (cement): 1.8 (sand): 0.38 (water). In the other mixes, the cement was partially replaced with 15% and 30% slag of different fineness of 350, 420, and 500 m2/kg. The other constituents remained unchanged. Testing included slump flow, V-funnel flow time, yield stress and viscosity, compressive strength, total and autogenous shrinkage, and capillary water absorption. The presence of slag was found to reduce the plastic viscosity and yield stress of SCM mixtures as the content and the fineness increase. The higher the fineness (specific surface) of the slag the less the rheological parameters (i.e. slump flow and viscosity). The results show also a reduction in compressive strength of SCM at early ages of curing in the presence of slag. However, in the long-term, the compressive strength of SCM mixtures containing slag was higher than that of control mortar. Generally, there is reduction in the total shrinkage and an increase in the autogenous shrinkage of SCM mixtures as the content and fineness increase. Doi: 10.28991/cej-2021-03091694 Full Text: PDF